Audit of Gynaecological hysterectomies - Fayyaz, Simi; Majid, Shamim S. (Journal of Postgraduate Medical Institute, 2011)
One year audit of Gynaecological hysterectomies was carried out in Gynae B department, LRH, Peshawar. Among the patients admitted for major gynaecological operations, those undergoing hysterectomy were entered in to study programme. The incidence of hysterectomy among major operations was almost 50%. The indications for hysterectomy were evaluated. Patients were studied and observed preoperatively, intraoperatively and postoperatively till thier stay in hospital. the follow up visit was also recoreded with histopathology report after 6 weeks. Ratio of abdominal to vaginal route was almost 2:1 with higher complication rate and postoperative hospital stay in former group. Most of the operations were done electively. Majority of indications were benign in which surgery could be avoided reflecting non availability of other effective medical and conservative surgical treatment modalities. Need to increase the number of vaginal hysterectomies was also noticed in teh audit. With all these limitations in our setup hysterectomy proved curative and acceptable form of therapy to most of the patients.